Strategies in Forestry to Combat Global Climate Change - Singh, Ombir; Panwar, Vijender Pal; Shandilya, Manish Dev (Indian Forester, 2021)
Populations with little genetic variation are more vulnerable to the arrival of new pests or diseases, pollution, changes of climate and habitat destruction or other catastrophic events. Biological diversity is the best tool to counter environmental changes and combat climate change in uncertain future. Spatial isolation, fragmentation, increased in-breeding, low fruit set in disturbed natural forests necessitates more population sizes to generate enough variability through mutation and recombination's. Planting a diverse array of species and seed sources is a hedge in the face of global climate change. The best plantation strategy is to maintain diversity, breed for generalists, and deploy intimate mixtures of seed sources or progeny-tested families. Flowering time and seed maturation in plants could be altered in the scenario of climate change; so, should be understood and taken care off. In the era of climate change, conservation of forest genetic resources and their management is necessary to maintain required biodiversity to combat climate change. Seed banking is also a tool in combating the loss of global plant diversity.